Improving land management mechanism cities to housing development (in the Tver region) - A. V. Vlasov; O. I. Lebedeva (Путеводитель предпринимателя, 2020)
The article describes aspects of the city’s land for development of housing construction in the Tver region. Particular attention is given to the current legal and economic basis of housing in the region.